2021
DOI: 10.1002/cche.10416
|View full text |Cite
|
Sign up to set email alerts
|

Different preparation methods affect the phenolic profiles and antioxidant properties of Qingke barley foods

Abstract: Background and objectives Barley is rich in bioactive compounds and can prevent some chronic diseases. With the increasing health awareness of the consumers, Qingke barley has been widely consumed in China in the Qingke barley fresh noodles (QBFN), Qingke barley dried noodles (QBDN), Qingke barley bread (QBB), and Qingke barley Chinese steamed bread (QBSB) forms. Preparation methods affect the phenolic profiles, content, and antioxidant capacity of these products. In this work, phenolic profiles and antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This work may provide new research ideas for developing new food originating bioactive compounds using in vitro and in silico methods. acid, chlorogenic acid, vanillic acid, syringic acid, p-coumaric acid, rutin, ferulic acid, naringin, epicatechin, o-coumaric acid, quercetin, naringenin, kaempferol in Qingke barley fresh noodles (Figure S1, has been published) (Tuersuntuoheti et al, 2021). According to previous studies, we hypothesized that these phenolic compounds also could reduce the blood sugar level by inhibiting DPP-IV activity.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…This work may provide new research ideas for developing new food originating bioactive compounds using in vitro and in silico methods. acid, chlorogenic acid, vanillic acid, syringic acid, p-coumaric acid, rutin, ferulic acid, naringin, epicatechin, o-coumaric acid, quercetin, naringenin, kaempferol in Qingke barley fresh noodles (Figure S1, has been published) (Tuersuntuoheti et al, 2021). According to previous studies, we hypothesized that these phenolic compounds also could reduce the blood sugar level by inhibiting DPP-IV activity.…”
Section: Introductionmentioning
confidence: 76%
“…Most studies attribute the hypoglycemic function of barley to β‐glucan, besides β‐glucan, there are abundant polyphenols in barley. In our previous research, we found that there were 14 kinds of phenolic compounds, including gallic acid, protocatechuic acid, chlorogenic acid, vanillic acid, syringic acid, p‐coumaric acid, rutin, ferulic acid, naringin, epicatechin, o‐coumaric acid, quercetin, naringenin, kaempferol in Qingke barley fresh noodles (Figure S1, has been published) (Tuersuntuoheti et al, 2021). According to previous studies, we hypothesized that these phenolic compounds also could reduce the blood sugar level by inhibiting DPP‐IV activity.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The bound phenols interact with macromolecules such as starch, protein, and lipid by covalent and noncovalent bonds (hydrogen bonds, hydrophobic, van der Waals forces, ionic interactions, etc.). The interactions are destroyed under certain conditions, such as alkaline/acid hydrolysis, fermentation, and heating, resulting in the release of more phenolics from the food matrix (Acosta‐Estrada et al, 2014; Tuersuntuoheti et al, 2021). As expected, the majority of phenolics were in the bound form.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, many kinds of cereal contain higher levels of phytochemicals than wheat, especially polyphenols ( 14 ). Polyphenols can scavenge free radicals in the body to achieve the effect of antioxidants ( 33 ), polyphenols can also play a role in lowering blood pressure, blood lipids, and cholesterol, it has a preventive effect on cardiovascular and cerebrovascular diseases and atherosclerosis ( 34 36 ). These polyphenols may also promote the slow digestion of starch by inhibiting digestive enzymes ( 37 ).…”
Section: Nutritional Properties Of Coarse Cerealsmentioning
confidence: 99%